Timing and rate of nitrogen fertilization influence maize yield and nitrogen use efficiency - Davies, Benjamin (PLoS One, 2020)
Timing and rate of nitrogen (N) fertilizer application can influence maize (Zea mays L.) grain yield, N uptake, and nitrogen use efficiency (NUE) parameters, but results have been inconsistent across the upper Midwest. This study compared single (fall and preplant) and split applications of differing N rates for maize under irrigated conditions on loamy sand at Becker, MN and under rainfed conditions on loam and clay loam soils at Lamberton, MN and Waseca, MN, respectively, in 2014 to 2016. Fall and preplant applications of N were applied at recommended and 125% of recommended rates (RN) according to University of Minnesota guidelines. Split-application treatments included a two-way (Sp, applied at 75% and 100% of RN) and a three-way split (TSp applied at 50%, 75%, and 100% of RN), with the total N rate equally split among application times. At Becker, maize grain yield with TSp was 12.6 to 15.7 Mg ha(-1) among years and significantly greater than that with fall or preplant treatments. The TSp treatment also improved agronomic efficiency (AE) and recovery efficiency (RE) by an average of 30% over fall or preplant treatments. At Lamberton, maize grain yield, AE and RE did not differ among treatments. However, TSp75 improved AE by 8.3 kg kg(-1) while producing comparable yields to fall and preplant treatments. At Waseca, Sp or TSp improved grain yield and AE compared with fall treatments. These results suggest that split applications of N can increase maize grain yield, AE, and RE on irrigated coarse-textured soils and applying N fertilizer near planting or as a split application can improve N management on non-irrigated clay loam soils.